Respuestas

2013-11-16T05:31:04+01:00
A) -4 [5x + (-8x + 4)] = 3(3x -16) -7
-4[5x - 8x +4] = 9x - 98 - 7
-20x + 32x -16 = 9x - 105
-20x +32x -16 -9x -105=0
3x - 121 = 0
x = 121/3

b) 54x - [16x - (30 - 24x)] = 8 (2 x +9)
54x - [ 16x -30 +24x ] = 16x + 72
54x - 16x +30 - 24x - 16x -72 = 0
-2x -42 =0
x = 42/2
X=21


c) - 4 (3x -5) - 8 = 16 - 2 (12 - 5x) - 24x
-12x +20 -8 = 16 - 24 + 10x -24x
-12x +20 - 8 -16 +24 -10x +24x =0
2x + 20 =0
x= -20/2
x = -10

d) - 6 (3x - 8) + 20x= - 4 (- x +10) - 12
-18x +48 +20x = 4x -40 -12
-18x +48 +20x -4x +40 +12 =0
-2x + 100 = 0 multiplico todo por (-1)
2x - 100 = 0
x = 100/2
x=50